Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2002)
This issue of Networks is particularly interesting for the wide variety of articles it includes. They range from a high school science teacher's report of the strategy she used to improve her students' reading comprehension and the statistically significant result of her intervention, through contributions co-authored by collaborating partners in different institutions, to a practitioner's "ruminations" that intermingle poetry and prose on the relationship between teaching and research . Together, they demonstrate the many ways in which practitioner inquiry can be approached as well as the variety of genres in which it can effectively be shared.